2021
DOI: 10.3390/educsci11060259
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Problem-Based Projects in Cross-Disciplinary Student Teams

Abstract: This paper explores how engineering students and Work and Welfare students reflect upon their own engagement in a one-week cross-disciplinary project. To develop a better understanding of what unfolds during these activities we collected data through anonymous surveys two consecutive years. Data from these 141 respondents were analysed using a learning history approach and are presented as narratives. Results show major disruptions and conflicts driving the student projects, exposing inviting confrontations, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…Through the solving of problems, the students acquire the necessary knowledge and understanding of the content (Savin-Baden 2008, p. 8). Tan (2005) and Ellingsen et al (2021) point out that the use of crossdisciplinary knowledge to provide solutions to the problem is also a prominent characteristic of PBL and that students must take into consideration knowledge from various disciplines, subjects and topics.…”
Section: Key Features Of Problem-based Learningmentioning
confidence: 99%
“…Through the solving of problems, the students acquire the necessary knowledge and understanding of the content (Savin-Baden 2008, p. 8). Tan (2005) and Ellingsen et al (2021) point out that the use of crossdisciplinary knowledge to provide solutions to the problem is also a prominent characteristic of PBL and that students must take into consideration knowledge from various disciplines, subjects and topics.…”
Section: Key Features Of Problem-based Learningmentioning
confidence: 99%
“…Salah satu upaya yang perlu dilakukan ialah mengembangkan kemampuan mahasiswa dalam higher order thinking skill (HOTS) yang menjadi dasar untuk pengembangan kompetensi profesional (Brad Hokanson, 2018;Jonathan Haber, 2020). Selain kemampuan berpikir, perlu juga memanfaatkan teknologi informasi dan komunikasi sesuai tuntutan dunia usaha (Siti Martiah, 2017), dan penugasan melalui pembelajaran berbasis projek perlu dilakukan untuk mengembangkan higher order thinking skills sebagaimana dibuktikan dari penelitian Ellingsen et al (2021).…”
Section: Fakultas Ekonomi Bisnis Pada Universitasunclassified
“…Untuk itu dibutuhkan pula metode pembelajaran yang tepat sesuai dengan kompetensi hasil belajar yang akan dicapai (John Almarode & Kara Vandas, 2018). Salah satu metode yang tepat untuk itu ialah metode team based project (Ellingsen et al, 2021). Team based project merupakan metode yang memberikan kegiatan belajar dan penugasan nyata berbasis proyek sebagai tantangan bagi mahasiswa untuk dipecahkan secara berkelompok (Picard et al, 2022).…”
Section: Kajian Literaturunclassified
“…Project-based learning (PBL) is a collaborative and interactive instructional approach that allows students to engage actively in the classroom [35,36]. Prior studies [37][38][39] have identified that PBL has proved to be an effective strategy for promoting teamwork skills in the classroom [40]. PBL motivates students to think critically and improves knowledge construction [41].…”
Section: Hagermann and Klugementioning
confidence: 99%